From Pentecost to the Triune God: a Pentecostal Trinitarian theology - Studebaker, Steven M. (Pentecostal manifestos, 2012)
Pentecostal approach to the Trinity -- Holy Spirit and the Trinity -- Eastern and western trinitarian theology -- Reformed evangelical trinitarian theology -- Charismatic trinitarian theology -- Spirit of Pentecost and theology of religions -- Spirit of Pentecost and creation